The Aesthetic Concerns of Botulinum Toxin Type A in the Treatment of Neck Wrinkles: A Systematic Review. (21st November 2020) - Qiu, He; Zhao, Rui; Cao, Lideng; Liu, Shuo; Yu, Donglei; Wang, Hang
Abstract: Background: The aged and unattractive appearance of the neck has a profound impact on the overall youthfulness and attractiveness of the face. Neck wrinkles are one of the manifestations of neck skin aging. Botulinum toxin type A (BTX-A) represents an effective means for aesthetic neck rejuvenation as novel facial rejuvenation technologies are progressively developed. Objectives: The objective of this article was to review the pertinent clinical literature for descriptions of BTX-A treatments and evaluations of their efficacy and safety for neck wrinkles. Methods: The Web of Science, PubMed, EMBASE, Cochrane Library, and SCOPUS databases were searched from inception to April 30, 2020, for the existing literature, which is presented along with the authors' experience with neck wrinkles. Results: Overall, 112 women between 24 and 65 years of age were included in 3 studies of monotherapy and 2 studies of multimodal combination therapy. BTX-A has been reported in combination with other approaches, including intensity focused ultrasound, cohesive polydensified matrix hyaluronic acid, and microfocused ultrasound. Only 1 of the 3 reports on monotherapy had a less than 50% satisfaction and improvement rate. Overall, BTX-A attained high patient satisfaction without serious and persistent side effects, notwithstanding the relatively limited sample size. Conclusions: The existing research cannot strongly prove the aesthetic effect of BTX-A in neck wrinkles. However, BTX-A is probably an effective technology in response to the growing demand for neck wrinkle treatment, whether in a single treatment or combined treatment. Level of Evidence: 4: